Clinical, Histological, and Immunohistochemical Insights into a Canine Hepatic Myofibroblastic Sarcoma - Valentina Rinaldi; Laura Nordio; Massimo Vignoli; Stefano Masci; Lorenzo Ressel; Paolo Emidio Crisi (Veterinary Sciences, 2025)
Hepatic sarcomas are rare and aggressive tumors in veterinary medicine, with limited reports in the literature. This case report describes a canine hepatic myofibroblastic sarcoma in a 5-year-old spayed female Dobermann. The dog presented with abdominal enlargement and was diagnosed with a large hepatic mass following comprehensive diagnostic evaluations, including blood tests, imaging, and histopathology. Histological and immunohistochemical analyses confirmed the tumor’s myofibroblastic origin, characterized by positivity for markers such as vimentin, glial fibrillary acidic protein (GFAP), nerve growth factor receptor (NGFR), alpha-smooth muscle actin (SMA), and muscular actin (HHF35). Treatment involved a combination of intense-dose chemotherapy using doxorubicin and a subsequent metronomic chemotherapy protocol, which resulted in prolonged survival of over 690 days at the time this manuscript was written. This case highlights the importance of extensive diagnostic and immunohistochemical profiling in the accurate classification of and treatment planning for hepatic sarcomas, and emphasizes the role of advanced veterinary diagnostics in improving patient outcomes. Future studies with larger sample sizes are needed to enhance understanding of the biological behavior and optimal therapeutic strategies for such rare tumors.